Peran Orang Tua Dalam Pendidikan Informal (Perspektif Pendidikan Agama Hindu) - I Nyoman Temon Astawa (Jayapangus Press, 2022)
Education is oriented identically to the school world and connects teachers with students. Students learn a lot at home from their parents regarding various things that are needed in their growth, towards maturity and maturity. It is in the family that the child first receives education, which is the most important or primary for the child's personal development. The first education for a child is received from the family so that the role of the family in shaping a child's moral character becomes very important. The family actually has an educational process going on, and of course the system used is different from the system applied to formal education with strict and firm regulations. Based on this phenomenon, researchers will examine the role of parents in informal Hindu religious education. This study uses data collection techniques of observation, interviews, literature study and documentation. Meanwhile, the data processing method uses flow analysis from Milles and Hubberman by paying attention to the quality of the problems discussed. The main aspect of the system is that the pattern of informal education aims to provide a foundation or foundation for children about the teachings of Hinduism. The implementation of informal education takes place within the family environment for individuals, training and religious activities. The context or content of Hindu religious teaching materials to familiarize children in carrying out religious activities. The aim is to provide an understanding of Hinduism from an early age through the educational process in the family, the meaning obtained with sufficient understanding of children is expected to be able to increase sradha and devotion. The quality of human resources is the main key to progress and develop. The environment contributes significantly to the development of children. The most vital economy in the implementation of Hindu religious informal education. Individual, social, and emotional factors play a very decisive role. Intrinsic motivation such as the condition of parents and the quality of human resources is very important to be harmonized to obtain satisfactory educational results. The findings in this study are that parents have a strategic role in determining and shaping the character and character of children through education in the family. These roles are parents as the main and first teacher in the family, parents as mentors of children in the family and parents as facilitators, dynamists, motivators and evaluators in giving Hindu religious lessons in the family environment. These roles are facilitating, providing dynamics, providing motivation and evaluating the results of education.